2011
DOI: 10.1111/j.1365-294x.2011.05272.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of wild and laboratory zebrafish (Danio rerio)

Abstract: Understanding a wider range of genotype–phenotype associations can be achieved through ecological and evolutionary studies of traditional laboratory models. Here, we conducted the first large-scale geographic analysis of genetic variation within and among wild zebrafish (Danio rerio) populations occurring in Nepal, India, and Bangladesh, and we genetically compared wild populations to several commonly used lab strains. We examined genetic variation at 1832 polymorphic EST-based single nucleotide polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 97 publications
4
92
2
1
Order By: Relevance
“…Results (see Figure S5) identified 14 SNPs that were shared across all our strains and all fish of haplogroup 1 but were absent from all haplogroups 2 and 3, showing that NA, WIK, EKW, and CB all derived from haplogroup 1 (Whiteley et al 2011). Among the six strains we used and the 16 populations in the Whiteley et al (2011) study, only AB appeared in both studies, and in both cases was in haplogroup 1. We conclude that our samples represent a single branch of the broad diversity of mitochondrial lineages across the zebrafish species.…”
Section: Phylogenomics Of Sex Determinant Lossmentioning
confidence: 98%
See 3 more Smart Citations
“…Results (see Figure S5) identified 14 SNPs that were shared across all our strains and all fish of haplogroup 1 but were absent from all haplogroups 2 and 3, showing that NA, WIK, EKW, and CB all derived from haplogroup 1 (Whiteley et al 2011). Among the six strains we used and the 16 populations in the Whiteley et al (2011) study, only AB appeared in both studies, and in both cases was in haplogroup 1. We conclude that our samples represent a single branch of the broad diversity of mitochondrial lineages across the zebrafish species.…”
Section: Phylogenomics Of Sex Determinant Lossmentioning
confidence: 98%
“…Analysis of the mitochondrial genome-encoded cytb gene showed that our strains all derived from mitochondrial haplogroup 1, suggesting that a broader understanding of the genetics of sex determination across the full diversity of zebrafish will require investigations of haplogroups 2 and 3 (populations in Nepal and Southern India, respectively), which diverged from haplogroup 1 about 3 million years ago (Whiteley et al 2011). Investigations of Danio species closely related to zebrafish will also add to our understanding, although the sar4 sexdetermination locus may not be widely conserved with other danios.…”
Section: Domesticated Zebrafish Strains Lack a Single Strong Sexlinkementioning
confidence: 99%
See 2 more Smart Citations
“…Pritchard et al (2000) use three examples: simulated data, data sampled from three geographically distinct groups of Taita Thrush, and data from African and European humans. Thus, the genetic data used by Structure might come from theoretical populations (e.g., simulations), laboratory populations (e.g., Whiteley et al, 2011), or natural populations. Structure uses genetic data to estimate populations.…”
Section: How To Avoid Conflating Theoretical With Natural Populationsmentioning
confidence: 99%